Conducting genetic epidemiology research on hyperuricaemia and gout in an indigenous community in Guam - a feasibility study - Yvette C. Paulino; Frank Camacho; Tristan VC Paulino; Delores J. Lee; Lisa Linda Natividad; Elizabeth Matisoo-Smith; Tony R. Merriman; Anna L. Gosling (BMC Public Health)
Abstract Background Gout, the most common inflammatory arthritis disease, and hyperuricaemia onset are influenced by environmental and genetic factors. We sought to investigate these factors in an Indigenous community in Guam. Methods In this feasibility study, the University of Guam led the qualitative inquiry with the native community, training (pre-screening of participants, data collection methods, and biospecimen handling), study implementation (outreach and recruitment, data collection, and DNA extraction and quantification), and qualitative and epidemiologic data analyses. Recruitment targets were based on demographic representation in current census data. The University of Otago collaborated on ethics guidance, working with Indigenous communities, and led the genetic sequencing and genetic data analysis. Participants were recruited in Guam from Fall 2019 to Spring 2022. Results Of the 359 participants, most self-identified as Native CHamorus (61.6%) followed by Other Micronesians (22.0%), and Filipinos (15.6%). The prevalence of metabolic conditions from highest to lowest were obesity (55.6%), hyperuricaemia (36.0%), hypertension (27.8%), gout (23.0%), diabetes (14.9%), cardiovascular disease (8.4%), kidney disease (7.3%), and liver disease (3.4%). There was variation in the prevalence of metabolic conditions among the major ethnic groups in this study. Conclusions We estimated the prevalence of metabolic conditions, especially gout and hyperuricaemia, and found variation among ethnic groups, all while obtaining the Indigenous community’s feedback on the genetic study and building gout research capacity. The results of ongoing genetic sequencing will be used to understand molecular causes of gout in Guam.